Improving The Students’ Ability in Understanding Reading Text by Using Small Group Discussion at Assalam Islamic Boarding School - Suparman, Suparman (JUPE : Jurnal Pendidikan Mandala, 2024)
This study investigates the effectiveness of using small group discussions to enhance students' ability to understand reading texts improving the students’ ability in understanding reading text by using small group discussion at Assalam Islamic Boarding School of Sumbawa, employing the action research classroom method. The primary aim is to address the difficulties students encounter in reading comprehension and to assess the impact of collaborative learning strategies on their performance. The research was conducted in cycles, each consisting of planning, action, observation, and reflection phases. During the planning phase, lesson plans incorporating small group discussions were developed. In the action phase, these plans were implemented in the classroom. Observations and reflections were conducted to evaluate student engagement and comprehension levels, with adjustments made in subsequent cycles to optimize learning outcomes.Data collection involved pre-tests and post-tests to measure improvements in students' reading comprehension, as well as qualitative observations and student feedback. The results of the research indicate that implementing small group discussions can address students' difficulties in understanding texts. Based on observations, interviews, test results, and the researcher’s field notes, the following findings were observed: (1) Small group discussions can enhance students' ability to comprehend texts. This improvement in understanding can be seen by comparing the average scores of the pre-test and post-tests from cycles. The average score of the pre-test was 66.42, and post-test was 68.75. (2) The advantages of using small group discussions in teaching reading are: (a) small group discussions encourage active student participation; (b) small group discussions create an enjoyable and interesting classroom atmosphere; and (c) small group discussions provide students with the opportunity to engage in discussions about the reading text. (3) The challenges of using small group discussions in teaching reading are: (a) students tend to use their native language during discussions; (b) additional preparation is required before implementing small group discussions; and (c) it takes considerable time to prepare for small group discussion